Mechanical characterization of PDMS with different mixing ratios - Sales, Flaminio C.P. (2022)
Polydimethylsiloxane (PDMS) is a transparent, biocompatible, flexible, simple processing, chemically and thermally stable polymer that has been attracting attention due to its wide range of applications in mechanical, civil and electronic engineering and biomedical field. In order to improve PDMS’ properties, many studies have been investigating the effect of the mixing ratios of its components (base polymer and curing agent) on the mechanical properties, once they affect the number of interactions between the polymer chains of the material. With the aim to make a comparison of the mechanical response of pure PDMS (SYLGARD 184) with different ratios of the base elastomer and the curing agent, tensile and hardness tests were performed. The tested mixing ratios were 10:1, 10:2 and 10:3 (base: curing agent). Tensile tests were executed in a universal tester machine, set up with a velocity of 500 mm/min and pre-load of 1 N. An analogical portable durometer type Shore A was used to carry out the hardness test, according to ASTM D2240. The results for the tensile test showed that an increase in the amount of cure agent reduced the tensile strength. The hardness values obtained were 41.7±0.95, 43.2±1.03 and 37.2±1.14 Shore A for pure PDMS with ratios equal to 10:1, 10:2 and 10:3, respectively.